2014
DOI: 10.1074/jbc.m113.538751
|View full text |Cite
|
Sign up to set email alerts
|

Role of Promyelocytic Leukemia Zinc Finger (PLZF) in Cell Proliferation and Cyclin-dependent Kinase Inhibitor 1A (p21WAF/CDKN1A) Gene Repression

Abstract: Background: Promyelocytic leukemia zinc finger (PLZF) is transcription repressor that recruits nuclear co-repressors at the target promoters. PLZF is overexpressed in various human solid tumors, such as clear cell renal carcinoma, glioblastoma, and seminoma. Results: PLZF represses transcription of CDKN1A by inhibition of p53 acetylation, Sp1 binding. Conclusion: PLZF causes cellular transformation and increases cell proliferation by repressing transcription of CDKN1A. Significance: PLZF can act as a proto-onc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 36 publications
4
27
0
2
Order By: Relevance
“…Previous investigations have demonstrated a pleiotropic regulatory role for PLZF in a myriad of developmental programs and physiological responses, from hind-limb skeletal patterning [ 11 ] to spermatogonial stem-cell maintenance [ 18 , 19 ]. Due to its role in limiting cell-cycle progression and cellular proliferation [ 20 , 21 ], PLZF is known to act as a tumor suppressor in a broad spectrum of malignancies [ 22 26 ]. At the transcriptional level, PLZF is known primarily as a repressor; reviewed in [ 16 ]; however, an increasing number of studies describe PLZF as an activator of transcription [ 27 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations have demonstrated a pleiotropic regulatory role for PLZF in a myriad of developmental programs and physiological responses, from hind-limb skeletal patterning [ 11 ] to spermatogonial stem-cell maintenance [ 18 , 19 ]. Due to its role in limiting cell-cycle progression and cellular proliferation [ 20 , 21 ], PLZF is known to act as a tumor suppressor in a broad spectrum of malignancies [ 22 26 ]. At the transcriptional level, PLZF is known primarily as a repressor; reviewed in [ 16 ]; however, an increasing number of studies describe PLZF as an activator of transcription [ 27 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although overexpression of PLZF leads to a block of cell cycle progression in a myelomonocytic cell line (U937T) (38), it was recently described that PLZF expression may stimulate proliferation in NIH3T3 cells by repressing expression of Cdkn1a (p21), a negative regulator of cell cycle progression (39), however, we did not find increased Cdkn1a levels in PLZF-deficient Vγ6 + γδT-cells ( data not shown ), indicating that PLZF is required for other mechanisms of cell cycle control in Vγ6 + γδT-cells.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of p21 may also inhibit CDK1 and prevent G2/M transition. Moreover, p21 has also been demonstrated to inhibit the kinase activity of cyclin A/CDK2, thereby inhibiting the cell cycle through S phase arrest (28,29). Therefore, numerus studies have shown that p21 plays a central role in carcinogenesis-associated cell cycle regulation and DNA repair (30).…”
Section: Discussionmentioning
confidence: 99%